2020
DOI: 10.4252/wjsc.v12.i7.659
|View full text |Cite
|
Sign up to set email alerts
|

Role of stem cell therapies in treating chronic wounds: A systematic review

Abstract: BACKGROUND The impairment of cutaneous wound healing results in chronic, non-healing wounds that are caused by altered wound environment oxygenation, tissue injury, and permissive microbial growth. Current modalities for the treatment of these wounds inadequately address the complex changes involved in chronic wound pathogenesis. Consequently, stem cell therapies have emerged as a potential therapeutic modality to promote cutaneous regeneration through trophic and paracrine activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 107 publications
0
33
0
2
Order By: Relevance
“…Moreover, addition of hASCs in comparison to hydrogel treatment alone increased the M2/M1 macrophage ratio, suggesting that hASCs can promote the transition to the repair phase of healing (252). A recent systematic review by Raghuram et al, identified adipose-derived stem cells, bone marrow-derived stem cells, bone marrow-derived mononuclear cells, epidermally derived mesenchymal stem cells, fibroblast stem cells, keratinocyte stem cells, placental mesenchymal stem cells, and umbilical cord mesenchymal stem cells being used in vitro and in vivo as potential treatments for chronic wounds, however, clinical effectiveness still requires investigation due to heterogeneity of wound etiology (253).…”
Section: Promoting Macrophage Polarization Towards An M2 Phenotypementioning
confidence: 99%
“…Moreover, addition of hASCs in comparison to hydrogel treatment alone increased the M2/M1 macrophage ratio, suggesting that hASCs can promote the transition to the repair phase of healing (252). A recent systematic review by Raghuram et al, identified adipose-derived stem cells, bone marrow-derived stem cells, bone marrow-derived mononuclear cells, epidermally derived mesenchymal stem cells, fibroblast stem cells, keratinocyte stem cells, placental mesenchymal stem cells, and umbilical cord mesenchymal stem cells being used in vitro and in vivo as potential treatments for chronic wounds, however, clinical effectiveness still requires investigation due to heterogeneity of wound etiology (253).…”
Section: Promoting Macrophage Polarization Towards An M2 Phenotypementioning
confidence: 99%
“…The study further states that exosomes derived from human ESCs can behave like their parental ESCs and contribute to antiaging and regenerative medicine via transfer and encapsulation of bioactive molecules to target cells. Although in vivo study of ESCs shows promising results in wound healing, its clinical use is limited by the ethical controversy revolving their procurement process as it can induce damage to the human embryo [ 62 ]. Instead, much interest is being developed towards ASCs and iPSCs as they possess minimal ethical concerns relating to procurement and clinical translation.…”
Section: Components Of Skin Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Apart from MSCs and ASCs, bone marrow-derived stem cells (BM-SCs), and human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) are good candidates for the treatment of different types of wounds [ 11 ]. hUC-MSC isolated from umbilical cord lining tissue represents another mesenchymal stem cell population [ 62 ]. Notably, the epithelial cells belonging to the umbilical cord possess stem cell-like properties and can differentiate into any form of stratified epithelium required for improved wound healing [ 56 ].…”
Section: Components Of Skin Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…15,42 Fatty tissue, for instance, harbors the potential to differentiate and to regenerate as it contains adipose derived stem cells. 43 These abilities have been used to treat and rehabilitate scars from burns and irradiation elsewhere in the body. [43][44][45] Remodeling of contracted atrophic soft tissue scars using autologous fat transfer in rhinoplasty has been described.…”
Section: Thick Skinmentioning
confidence: 99%
“…43 These abilities have been used to treat and rehabilitate scars from burns and irradiation elsewhere in the body. [43][44][45] Remodeling of contracted atrophic soft tissue scars using autologous fat transfer in rhinoplasty has been described. 42 The autologous fat transfer can be either injected preoperatively or intraoperatively using the microfat-infused soft tissue augmentation (MISTA) technique as described by Toriumi.…”
Section: Thick Skinmentioning
confidence: 99%